Associations between perfectionism, procrastination and academic performance of students at an international school in Selangor - Nadarajah, Thanamani; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This study aims to examine the associations between procrastination, perfectionism and academic performance of students at an international school in Selangor. A total of 85 Year 7, Year 8 and Year 9 students took part in this study. Lay’s Procrastination Scale (1986) and Frost’s Multidimensional Perfectionism scale (1990) were used as instruments in this research. For academic achievement, mean value of student’s marks from their final examination was calculated. This study employs a quantitative method where a survey questionnaire were distributed to students. Descriptive data analysis was performed to calculate means and standard deviations. Inferential statistical analyses using a series of logistic regressions were conducted to predict students’ academic achievement level based on categorical predictor variables. Since the analyses are still on-going at this stage, this paper therefore reports the preliminary descriptive findings. Upon completion of data analysis, it is expected that there that will be significant associations between different levels of procrastination and perfectionism and different levels of students’ academic achievement.